Effect of coupling agent and alkali treatment on mechanical, thermal and morphological properties of flax-fiber-reinforced PLA composites - Avci, Ali; Eker, Aysegul Akdogan; Bodur, Mehmet Safa (EMERALD GROUP PUBLISHING LTD, 2021)
In the current study, three different types of biocomposites based on poly(lactic acid) (PLA) and short flax fiber were produced using extrusion. Alkali treatment was conducted on the flax fiber before the extrusion process in order to improve the interfacial adhesion between the flax fiber and the PLA matrix. The influence of the coupling agent and alkali treatment on the composite materials was investigated with regard to the mechanical, thermal and thermomechanical properties of the injected composites. The results show that the coupling agent has a favorable effect on the thermal, thermomechanical and mechanical properties of the composites. The flexural and tensile moduli of the composites were significantly enhanced compared with those of pure PLA samples. Dynamic mechanical thermal analysis and thermogravimetric analysis (TGA) results indicate that the loss and storage modulus of PLA/flax fiber composites are increased compared with those of both pure PLA and composites with the coupling agent. The TGA showed that the thermal stability of PLA improved with the addition of flax fiber into PLA. Additionally, the developed flax fiber content in PLA with the coupling agent improved the tensile, flexural strength and flexural modulus. The tensile strength of the alkali-treated flax fiber increased up to 50MPa compared with that of the untreated flax fiber. The Fourier transform infrared spectroscopy method was carried out to examine the chemical composition of the composite and interaction of functional groups for both alkali-treated and untreated flax fibers.
Keywords: composite materials; green polymers; poly(lactic acid); NATURAL FIBER; SURFACE MODIFICATIONS; GREEN COMPOSITES; SILANE TREATMENT; BLENDS; POLYLACTIDE; PERFORMANCE; TENSILE; IMPACT; Science & Technology - Other Topics; Materials Science; Polymer Science